PERBANDINGAN TINGKAT ADIKSI GAME ONLINE DENGAN TINGKAT AGRESIVITAS PADA REMAJA SEKOLAH MENENGAH PERTAMA - Asari, Honest Vania; Liza, Rini Gusya; Isrona, Laila (LPPM Institut Pendidikan Nusantara Global, 2024)
Aggressive behavior is an act of non-physical or physical force that intended to cause harm. Aggressive behavior in adolescents is a global public health problem. It includes a range of acts from acts of intimidation, physical fights, even a murder. In Indonesia, there has been an increase in cases of aggressive behavior in teenagers from 321 cases in 2021 to 1451 cases in 2020.Studies have shown multiple factors within a person that may contribute to aggressive behavior, including an addiction to online games. An excessive increase in dopamine due to online game addiction causes a decrease in dopamine D2 receptors (D2DRs) in the prefrontal cortex. This causes dysfunction of the prefrontal cortex which can lead to aggressive behavior The aim of the study was the investigation of the addictive potential of gaming as well as the relationship between online game addiction and aggressive behavior. A cross-sectional study was conducted using Indonesia Online Game Addiction Questionnaire (IOGAQ) and Buss-Perry Agression Questionnaire (BPAQ). The sample consisted of 133 students of SMPN 1 Lubuk Sikaping, using total sampling technique. Data revealed that 58,6% of students fulfilled diagnostic criteria of online game addiction (mild to severe category) and 56,4% of students had moderate levels of aggression. The study concluded that there is a correlation between online game addiction and aggressive behavior (p-value = 0.000).